The Role of Work Experience in Moderating Independence and Competence on Internal Audit Effectiveness - Rizka Fitriasari; Muhammad Aidhil Firmansyah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study examines the effect of auditor independence and competence on internal audit effectiveness, with work experience as a moderating variable, in the context of public sector auditing in Indonesia. Strengthening internal audit effectiveness is essential to ensure good governance and accountability in government institutions. This study aims to analyze the influence of auditor independence and competence on internal audit effectiveness and to test the moderating role of work experience. An explanatory quantitative approach was employed, using questionnaire data from 156 internal auditors of the Financial and Development Supervisory Agency (BPKP) across Indonesia, analyzed with Moderated Regression Analysis (MRA). The results show that auditor independence and competence have a significant positive effect on internal audit effectiveness. However, work experience does not significantly moderate the relationship between independence and internal audit effectiveness, nor between competence and internal audit effectiveness. These findings indicate that improving internal audit effectiveness is primarily driven by strengthening auditor independence and competence, while work experience does not play a significant moderating role.